Atmospheric chemistry and global change - Guy P Brasseur; Orlando, John P; Tyndall, Geoffrey S. (New York Oxford University Press, 1999)
Atmospheric Chemistry and Global Change presents an integrated examination of chemical processes in the atmosphere, focusing on global-scale problems and their role in the evolution of the Earth system. Taking a largely interdisciplinary approach, it features the collective efforts of a group of scientists at the National Center for Atmospheric Research (NCAR), as well as other experts from several universities and national laboratories. Topics discussed include the fundamental physical, chemical, and biological processes that affect the atmospheric composition; the chemical mechanisms that affect the production and the fate of important chemical compounds; and the techniques used to investigate the chemical processes in the atmosphere. The book concludes with discussions on global problems related to the atmosphere (stratospheric ozone depletion, changes in greenhouse gases, and global chemical pollution), the relationship between the atmosphere and the global climate, and the long-term chemical evolution of the atmosphere. Each chapter features a brief essay by a leader in the field and includes a large number of current references. Ideal for graduate courses in atmospheric chemistry and atmospheric science, Atmospheric Chemistry and Global Change also serves as an authoritative and practical reference for scientists studying the Earth's atmosphere.
Keywords: Chemistry